The Vishṇukuṇḍis and their times : an epigraphical study - Sankaranarayanan, S., 1926- (Agam Prakashan ; distributed by D.K. Publishers' Distributors, 1977)
Study on the Viṣṇukuṇḍis, south Indian dynasty, ruling from Srisaila, 375-612.